Comparing functions of copulation calls in wild olive baboons, Papio anubis, using multimodel inference - Bouquet, Yaëlle; Stephan, Claudia; Johnson, Caley A.; Rothman, Jessica M.; Neumann, Christof; Zuberbühler, Klaus; et al. (Animal Behaviour, 2018)
Female copulation calls are species specific, distinct vocal signals sometimes given during or shortly after mating. Despite being common in primates and despite much empirical work, their function remains largely unclear for most species. Here, we used an information-theoretic approach to examine simultaneously three main competing hypotheses for the evolution of copulation calls. Two of the three hypotheses predict that female copulation calls function to incite competition between males, either directly (the male–male competition hypothesis) or indirectly (the sperm competition hypothesis), while the third predicts that females use calls to choose mating partners (the female choice hypothesis). We collected data on copulations of wild female olive baboons in Kibale National Park, Uganda, to compare the relative support for these hypotheses by modelling whether or not females produced copulation calls after mounts. Our analytical approach enabled us to objectively rank models corresponding to the three hypotheses according to how well our data fitted the models. Our data favoured the sperm competition hypothesis over the female choice hypothesis although much variation in calling remained unexplained. The male–male competition hypothesis seems unlikely given our data. We also discuss the possibility that copulation calls have no function, functions not included in our analysis, or that they are multifunctional, a reflection of the species' social evolution history.<br
Keywords: copulation call; female choice; male–male competition; model ranking; multi-model inference; olive baboon; Papio anubis; sperm competition